Analisis Bahan Ajar IPAS pada Kurikulum Merdeka Kelas V SD di Kecamatan Kebonagung Demak - Aksari, Ika Hardiyan; Fakhriyah, Fina; Khamdun, Khamdun (Multidisciplinary Journal of Education , Economic and Culture, 2025)
The purpose of this study was to identify the strengths and weaknesses of the fifth grade IPAS teaching materials used in elementary schools based on the independent curriculum in more detail, so as to provide more specific recommendations for improvement. The aspects in analyzing this teaching material are content feasibility, language feasibility, presentation feasibility, and graphical feasibility. The flow of this research was carried out with the following steps. First, researchers formulated research problems related to the feasibility of teaching materials. Then, a checklist sheet was prepared as a data collection instrument. After that, researchers analyzed the teaching materials in depth using the checklist sheet. The data obtained were then analyzed qualitatively. The results of this study show that the two teaching materials each have their advantages and disadvantages. The aspects that met all the indicators of the two teaching materials were related to language feasibility.